Black sintered body and its manufacturing method

By controlling the pigment distribution and using carbonate-iron oxide solid solution, the problems of high pigment content and uneven color tone in the prior art are solved, and the preparation of black zirconium ceramics without tones is realized, and the pigment utilization rate and product stability are improved.

JP7671109B2Active Publication Date: 2025-05-01TOSOH CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2019140940
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-02
Filing Date
2019-07-31
Publication Date
2025-05-01
Estimated Expiration
2039-07-31

AI Technical Summary

Technical Problem

The prior art requires the use of a large number of pigments or new pigments when preparing black zirconium ceramic bodies, resulting in a high pigment content and making it difficult to achieve a black effect without a hue.

Method used

By controlling the distribution of pigments in the zirconium ceramic body, carbonate and iron oxides are used as pigments to form a carbonate-iron oxide solid solution, reducing the amount of pigment usage, and determining the distribution ratio of pigments through electron beam microscopy to achieve a tintless black effect.

Benefits of technology

With less pigment used, a black zirconium ceramic body without tones was prepared, which improved the pigment utilization rate and enhanced the color uniformity and stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671109000018
    Figure 0007671109000018
  • Figure 0007671109000019
    Figure 0007671109000019
  • Figure 0007671109000020
    Figure 0007671109000020
Patent Text Reader

Abstract

To provide a sintered body that reduces the content of coloring agent compared to a conventional sintered body, and exhibits color tone visible as a black color without assuming hue.SOLUTION: A sintered body includes a solid solution containing cobalt and iron, and the balance zirconia. A total amount of a content of cobalt in terms of CoO and a content of iron in terms of FeOis over 0.1 wt.% and less than 3.0 wt.%, and a percentage of the cobalt region over 5.5 μmoccupied in element mapping by an electron beam microanalyzer is equal to or less than 25%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sintered body containing a colorant and zirconia, and more particularly to a sintered body containing a colorant and zirconia and exhibiting a black color. [Background technology]

[0002] Conventionally, coloring of sintered bodies, that is, changing the color tone of zirconia sintered bodies from the inherent color tone of zirconia, has been studied. In order to obtain a black sintered body, a sintered body obtained by mixing and sintering a compound containing chromium (Cr) as a colorant with zirconia has been reported (for example, Patent Document 1). Patent Document 1 also discloses that a black sintered body can be obtained by mixing and sintering cobalt (Co) or iron (Fe) as a colorant with zirconia.

[0003] However, since chromium is an element that is difficult to handle, studies have been conducted on coloring sintered bodies without using chromium (Patent Documents 2 and 3). For example, a sintered body obtained by using cobalt oxide and iron oxide as colorants and firing this in air (Patent Document 2), and a sintered body containing a new colorant made of a Co-Zn-Fe-Al composite oxide (Patent Document 3) have been reported as black zirconia sintered bodies. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-342036 A [Patent Document 2] Japanese Patent Application Publication No. 07-291630 [Patent Document 3] JP 2007-308338 A Summary of the Invention [Problem to be solved by the invention]

[0005] Conventional sintered bodies have a black color due to the use of a large amount of colorant or a new colorant. In contrast, the present invention aims to provide a sintered body having a reduced content of colorant compared to conventional sintered bodies, and having a color tone that is visually recognized as a neutral black color (hereinafter also referred to as "jet black"). [Means for solving the problem]

[0006] The present inventors have discovered that by controlling the distribution state of the colorant in the sintered body, even a small amount of colorant can be used to make the sintered body appear jet black, and have thus completed the present invention.

[0007] That is, the gist of the present invention is as follows. [1] A solid solution containing cobalt and iron, with the remainder being zirconia, in which the total content of cobalt converted as CoO and iron converted as Fe2O3 is more than 0.1% by weight and less than 3.0% by weight, and the 5.5 μm area in elemental mapping by electron beam microanalyzer is less than 5.5 μm. 2 The sintered body according to claim 1, wherein the proportion of cobalt regions exceeding 25% is 0.05 or less. [2] 6.5μm in elemental mapping by electron probe microanalyser 2 The sintered body according to the above [1], wherein the proportion of iron regions exceeding this is 30% or less. [3] 5.0μm in elemental mapping by electron probe microanalyzer 2 The sintered body according to the above [1] or [2], wherein the proportion of iron regions exceeding this is 50% or less. [4] The sintered body according to any one of [1] to [3] above, which contains aluminum oxide. [5] The sintered body according to any one of the above [1] to [4], wherein the zirconia contains at least one selected from the group consisting of yttria, calcia, magnesia, vanadia and titania. [6] The sintered body according to any one of the above [1] to [5], wherein the zirconia is zirconia containing titania and yttria. [7] The sintered body according to any one of the above [1] to [6], wherein the zirconia contains 1.0 mol % or more and 6.0 mol % or less of titania and 2.0 mol % or more and 4.0 mol % or less of yttria. [8] The sintered body according to any one of the above [1] to [7], wherein the monoclinic rate of zirconia is 10% or less. [9] The sintered body according to any one of the above [1] to [8], wherein the average diameter of the zirconia crystal grains is 3.0 μm or less.

[10] A method for producing a sintered body according to any one of the above [1] to [9], comprising a sintering step of sintering in a reducing atmosphere a molded body containing a cobalt compound and an iron compound, with the remainder being zirconia, and in which the sum of the content of cobalt calculated as CoO and the content of iron calculated as Fe2O3 is more than 0.1 wt% and less than 3.0 wt%.

[11] The method according to the above

[10] , wherein the reducing atmosphere is an atmosphere using at least one of a reducing gas and a reducing heating element.

[12] The method according to the above

[10] or

[11] , wherein the sintering method in the sintering step is pressure sintering.

[13] The method according to any one of the above

[10] to

[12] , further comprising a pre-sintering step of sintering the green body in a non-reducing atmosphere to obtain a pre-sintered body.

[14] The method according to any one of the above

[10] to

[13] , further comprising a heat treatment step of heat treating the sintered body at 650°C or higher and 1100°C or lower in an oxidizing atmosphere. Effect of the Invention

[0008] According to the present invention, it is possible to provide a sintered body having a reduced colorant content as compared with conventional sintered bodies and exhibiting a jet black color. [Brief description of the drawings]

[0009] [Figure 1] Elemental mapping of Example 3 ((a) backscattered electron image, (b) Fe, (c) Co) [Diagram 2]Elemental mapping of Example 13 ((a) Elemental mapping of Co, (b) Elemental mapping after binarization) [Diagram 3] Elemental mapping of Example 13 ((a) Y, (b) Ti) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present invention will be described.

[0011] The sintered body of this embodiment contains a solid solution containing cobalt and iron (hereinafter also referred to as "Co-Fe solid solution"). The Co-Fe solid solution functions as a colorant that exhibits a black color. A sintered body that does not contain a Co-Fe solid solution and contains only iron or only cobalt has a different color tone from the sintered body of this embodiment, or is prone to defects, and therefore the sintered body of this embodiment cannot be obtained.

[0012] The Co-Fe solid solution in the sintered body of this embodiment can be confirmed by element mapping using an electron probe microanalyzer (hereinafter, simply referred to as "element mapping").

[0013] FIG. 1 is a diagram showing an example of element mapping of the sintered body of this embodiment. FIGS. 1(a) to 1(c) are a backscattered electron image of the sintered body (FIG. 1(a)), a mapping of iron (FIG. 1(b)), and a mapping of cobalt (FIG. 1(c)) in the same field of view. In the backscattered electron image, the base material zirconia and the Co-Fe solid solution are confirmed as light-colored regions (broken circle in FIG. 1(a)) and dark-colored regions (arrows in FIG. 1(a)), respectively. In FIG. 1(a), it can be confirmed that the Co-Fe solid solution is mainly distributed as approximately spherical regions having a diameter of 0.1 μm or more and less than 3.5 μm.

[0014] In the mapping of iron and cobalt, it can be seen that cobalt and iron are distributed in the same locations as the Co-Fe solid solution region in Fig. 1(a) (arrows in Figs. 1(a) to (c)). In Figs. 1(b) and (c), since cobalt and iron are contained in the roughly spherical regions in the backscattered electron images, it can be seen that the particles of the Co-Fe solid solution contain Co and Fe in a homogeneous solid solution. From Figs. 1(a) to (c), it can be seen that the Co-Fe solid solution is contained in the sintered body as particles, further as roughly spherical particles, and further as roughly spherical particles with a diameter of 0.1 μm or more and less than 3.5 μm.

[0015] One of the reasons why the sintered body of this embodiment contains the Co-Fe solid solution in such a distribution state is thought to be that cobalt and iron are incorporated into zirconia and form a solid solution, which then reprecipitates as fine particles from the zirconia particles.

[0016] The sintered body of this embodiment has a 5.5 μm 2 The ratio of the cobalt region exceeding (hereinafter also referred to as "Co distribution (5.5)") is 25% or less, preferably 20% or less, more preferably 10% or less, even more preferably 5% or less, and particularly preferably 3% or less. The Co distribution (5.5) is one of the indicators showing the distribution state of the Co-Fe solid solution in the sintered body of this embodiment. By containing cobalt and iron and showing such a Co distribution (5.5), the sintered body of this embodiment shows a color tone (jet black) that is visually recognized as a colorless black color.

[0017] In this embodiment, element mapping is performed using X μm 2 The proportion of the region of element M exceeding is hereinafter referred to as "M distribution (X)" and is represented as M distribution (X1), M distribution (X2), ..., M distribution (X n ) are collectively referred to as the "M distribution."

[0018] When there is uneven distribution of the Co-Fe solid solution to the extent that it affects the visible color tone, such as the presence of coarse particles in the Co-Fe solid solution or uneven distribution of the Co-Fe solid solution particles, the Co distribution (5.5) exceeds 25%. In other words, the presence of coarse particles or uneven distribution of particles increases the tendency of the sintered body to show uneven and non-uniform color tone or a color tone other than jet black. In addition, the presence of coarse particles or uneven distribution of particles makes it more likely that defects will occur during manufacturing.

[0019] For similar reasons, the Fe distribution (6.5) is preferably 30% or less, more preferably 25% or less, even more preferably 20% or less, even more preferably 10% or less, and particularly preferably 3% or less.

[0020] In the sintered body of this embodiment, it is preferable that the Co-Fe solid solution is distributed more uniformly, and it is preferable that at least one of the Co distribution and the Fe distribution shown below is satisfied.

[0021] Co distribution (5.0): 30% or less, preferably 25% or less, more preferably 15% or less, even more preferably 10% or less, particularly preferably 5% or less Co distribution (4.5): 35% or less, preferably 30% or less, more preferably 25% or less, even more preferably 10% or less, particularly preferably 5% or less. Co distribution (3.5): 55% or less, preferably 50% or less, more preferably 35% or less, even more preferably 15% or less, particularly preferably 8% or less Fe distribution (5.5): 45% or less, preferably 35% or less, more preferably 25% or less, even more preferably 15% or less, even more preferably 5% or less, particularly preferably 3.5% or less. Fe distribution (5.0): 50% or less, preferably 45% or less, more preferably 40% or less, even more preferably 20% or less, particularly preferably 5% or less. Fe distribution (4.5): 60% or less, preferably 50% or less, more preferably 15% or less, even more preferably 10% or less, particularly preferably 5% or less. Fe distribution (3.5): 70% or less, preferably 60% or less, more preferably 20% or less, even more preferably 15% or less, particularly preferably 10% or less. The sintered body of this embodiment has a 0 μm region in the cobalt region in element mapping. 2 Exceeds 2.0μm 2 The proportion of the region less than this value (hereinafter also referred to as the "most frequent Co region") is preferably 40% or more, and more preferably 80% or more.

[0022] The sintered body of this embodiment has a 0 μm area in the iron region in element mapping. 2 Exceeds 2.0μm 2 The proportion of the region containing less than 0.1% iron (hereinafter also referred to as the "modal Fe region") is preferably 50% or more, and more preferably 60% or more.

[0023] In the present embodiment, the element mapping is carried out by using a sintered body having a surface roughness (Ra) of 0.02 μm or less as a measurement sample and measuring element mapping for each element under the conditions shown below.

[0024] Measurement method: wavelength dispersion type Accelerating voltage: 15kV Irradiation current: 300nA Analysis area: 51.2μm×51.2μm Number of fields of view: 3 to 5 fields of view The M distribution, the most frequent Co region, and the most frequent Fe region can be determined from the obtained element mapping of each element by the following method.

[0025] FIG. 2 is a diagram showing an example of element mapping. The minimum intensity of the characteristic X-rays observed in the element mapping (FIG. 2(b)) obtained by binarizing the element mapping (FIG. 2(a)) of each element is regarded as the background intensity, and the number of regions (hereinafter also referred to as "detection regions"; for example, the arrows in FIG. 2(b)) in which the intensity of the characteristic X-rays is 1.5 times or more the background intensity, and the number of regions equivalent to the target area (hereinafter also referred to as "target regions") are counted. For example, the target region is 5.5 μm for Co(5.5). 2 If it is the most frequent Co region, it is 0 μm 2 Exceeds 2.0μm 2 It is an area less than.

[0026] The ratio of the number of target regions to the number of detection regions is calculated and this is taken as the distribution of each element. For example, the ratio of the number of regions where the intensity of the characteristic X-rays of cobalt is 1.5 times the background intensity to the number of regions where the intensity of the characteristic X-rays of 5.5 μm 2 The ratio of the number of regions occupying more than 5.0 μm is the Co distribution (5.5). 2 The percentage of the number of regions occupying this value or more is the Co distribution (5.0).

[0027] The binarization, detection of the detection region and the target region, and counting of the number of them can be performed by software attached to a general-purpose electron beam microanalyzer (e.g., EPMA System Ver. 2.14 manufactured by Shimadzu Corporation). An example of the electron beam microanalyzer is the EPMA1610 manufactured by Shimadzu Corporation. Since the measurement processing method is different, the detection region and the target region do not have to be the same in size as the Co-Fe solid solution confirmed by the backscattered electron image or element mapping.

[0028] The sintered body of this embodiment may contain at least one of cobalt oxide and iron oxide in addition to the Co-Fe solid solution.

[0029] In the sintered body of this embodiment, the total of the content of cobalt converted as CoO (hereinafter also referred to as the "cobalt content") and the content of iron converted as Fe2O3 (hereinafter also referred to as the "iron content") (hereinafter also referred to as the "colorant content") is more than 0.1% by weight and less than 3.0% by weight, preferably more than 0.1% by weight and less than 2.5% by weight, more preferably 0.12% by weight or more and 2.5% by weight or less, and even more preferably 0.2% by weight or more and 1.5% by weight or less. If the colorant content is 0.1% by weight or less, the color tone of the sintered body becomes grayish. If the colorant content is 3.0% by weight or more, defects during manufacturing and color tone variations from one piece to another are likely to occur, making it difficult to stably manufacture the sintered body of this embodiment.

[0030] Particularly preferred colorant contents in the sintered body of this embodiment include 0.1% by weight or more and less than 1.0% by weight, and further 0.2% by weight or more and less than 1.0% by weight.

[0031] In the sintered body of this embodiment, the cobalt content relative to the colorant content is preferably 0.10 or more and 0.98 or less, and more preferably 0.10 or more and 0.50 or less.

[0032] The sintered body of this embodiment may contain aluminum oxide, and preferably contains alumina (Al2O3). When aluminum oxide is contained, the content of aluminum converted to Al2O3 (hereinafter also referred to as "alumina content") is preferably 0.1% by weight or more and 3.0% by weight or less, more preferably 0.1% by weight or more and 2.5% by weight or less, more preferably 0.2% by weight or more and 2.5% by weight or less, even more preferably 0.1% by weight or more and 2.0% by weight or less, even more preferably 0.2% by weight or more and 2.0% by weight or less, even more preferably 0.1% by weight or more and 1.0% by weight or less, and particularly preferably 0.2% by weight or more and 1.0% by weight or less. If the content of aluminum oxide is 3.0% by weight or less, alumina hardly affects the color tone of the sintered body of this embodiment, and even if the colorant content is high, the generation of monoclinic zirconia tends to be suppressed. When containing aluminum oxide, the sintered body of this embodiment may contain a composite oxide of Al and Co, such as cobalt aluminate (CoAl2O4). The sintered body may contain a composite oxide such as cobalt aluminate, as long as the effect of the sintered body of this embodiment is not impaired.

[0033] The sintered body of this embodiment preferably does not contain impurities other than unavoidable impurities such as hafnium (Hf), and particularly preferably does not contain zinc (Zn) and chromium (Cr) (i.e., 0% by weight). The sintered body of this embodiment preferably has a zinc content converted into ZnO (hereinafter also referred to as the "zinc content") and a chromium content converted into Cr2O3 (hereinafter also referred to as the "chromium content") of less than 0.1% by weight, more preferably 0.05% by weight or less, and particularly preferably below the detection limit in general composition analysis (e.g., 0.005% by weight or less).

[0034] The sintered body of this embodiment is composed of the remainder zirconia. The sintered body of this embodiment has a content of zirconia converted into ZrO2 (hereinafter also referred to as "zirconia content") of 94.0% by weight or more, preferably 95.0% by weight or more, and more preferably 97.0% by weight or more.

[0035] In this embodiment, the cobalt content, iron content, colorant content, alumina content, zirconia content, zinc content and chromium content are each the weight percentage of each component relative to the weight of the sintered body of this embodiment.

[0036] The zirconia (ZrO2) contained in the sintered body of this embodiment is preferably zirconia containing at least one selected from the group consisting of yttria (Y2O3), calcia (CaO), magnesia (MgO), vanadia (BaO) and titania (TiO2) (hereinafter also referred to as "solid solution component"), and more preferably zirconia containing yttria. Since the particles of the Co-Fe solid solution in the sintered body tend to be fine, the zirconia is preferably zirconia containing at least one selected from the group consisting of calcia, magnesia, vanadia and titania and yttria, and more preferably zirconia containing titania and yttria. In addition, since the particles of the Co-Fe solid solution in the sintered body tend to be particularly fine, it is particularly preferable that the total content of cobalt converted as CoO and the content of iron converted as Fe2O3 is more than 0.1 wt% and 0.4 wt% or less, preferably more than 0.1 wt% and 0.3 wt% or less, and that the zirconia contains titania and yttria. In this embodiment, the finer the particles of the Co-Fe solid solution in the sintered body, the more easily the sintered body is visually recognized as having a uniform color tone.

[0037] The content of the solute components may be any amount that can dissolve in zirconia, and the content of each solute component may be, for example, 2.0 mol % or more and 10.0 mol % or less.

[0038] In this embodiment, the content of the solid solution component is the ratio (mol%) of each solid solution component to the total of zirconia and each solid solution component, and is a value calculated from [each solid solution component (mol)] / [each solid solution component (mol)+ZrO2(mol)]×100. For example, in zirconia containing yttria and titania, the yttria content (mol%) is a value calculated from [Y2O3(mol)] / [Y2O3(mol)+ZrO2(mol)]×100, and the titania content (mol%) is a value calculated from [TiO2(mol)] / [TiO2(mol)+ZrO2(mol)]×100.

[0039] For example, preferred contents of the respective solid solution components include at least any of the following.

[0040] Yttria content: 2.0 mol% or more and 4.0 mol% or less, preferably 2.5 mol% or more and 3.5 mol% or less Titania content: 1.0 mol% or more and 6.0 mol% or less, preferably 1.5 mol% or more and 4.8 mol% or less The sintered body of this embodiment preferably does not contain at least one of erbia (Er2O3) or ceria (CeO2), which is an element that dissolves in zirconia and significantly changes the color tone of the sintered body by dissolving in zirconia. The content of these elements is preferably below the detection limit, and taking into account measurement errors, etc., each of them can be, for example, 0 mol% or more and less than 1 mol%.

[0041] The sintered body of this embodiment preferably has an alumina content of 0.1% by weight or more and 2.0% by weight or less, further 0.1% by weight or more and 1.5% by weight or less, further 0.1% by weight or more and 1.0% by weight or less, and further 0.1% by weight or more and 0.5% by weight or less, and a titania content of 1.0% by weight or more and 4.0% by weight or less, further 1.0% by weight or more and 3.5% by weight or less, further 1.2% by weight or more and 3.2% by weight or less, and further 1.5% by weight or more and 3.0% by weight or less.

[0042] The zirconia crystal phase contained in the sintered body of this embodiment may be tetragonal or cubic as long as it has a tetragonal main phase. The main phase of the zirconia crystal phase contained in the sintered body of this embodiment is the phase that is most prevalent in the zirconia crystal phase in a powder X-ray diffraction (hereinafter also referred to as "XRD") pattern measured under the following conditions.

[0043] Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Step width: 0.02° Scan speed: 5° / min Measurement range: 2θ=20° to 80° In the sintered body of this embodiment, the XRD peak of the Co-Fe solid solution is not detected in the XRD pattern due to the content of the Co-Fe solid solution, etc. Therefore, the XRD pattern of the sintered body of this embodiment is the same as that of the zirconia crystal phase contained in the sintered body.

[0044] In the sintered body of this embodiment, the monoclinic ratio of zirconia is preferably 10% or less, more preferably 6.5% or less, even more preferably 2% or less, and even more preferably 1% or less.

[0045] The monoclinic ratio of zirconia is a value calculated from the XRD pattern of the surface of the sintered body of this embodiment measured under the above-mentioned conditions, using the following formula.

[0046] Monoclinic ratio (%) = [I m (111)+I m (11-1)] × 100 / [I m (111)+I m (11-1)+I t (111)+I c (111)] In the above formula, I m (111) is the surface intensity of the (111) plane of monoclinic zirconia, I m (11-1) is the surface intensity of the (11-1) plane of monoclinic zirconia, I t(111) is the surface intensity of the (111) plane of tetragonal zirconia, and I c (111) is the area intensity of the (111) plane of cubic zirconia.

[0047] The average diameter of the zirconia crystal grains contained in the sintered body of this embodiment (hereinafter also referred to as "average crystal grain size") is preferably 3.0 μm or less, more preferably 2.5 μm or less. Particularly preferred average crystal grain sizes include 0.3 μm to 2.5 μm, and further 0.5 μm to 1.3 μm.

[0048] In this embodiment, the average crystal grain size can be determined by observing the surface of the sintered body of this embodiment at a magnification of 15,000 times using a scanning microscope, randomly extracting 200 or more, preferably 250±50, zirconia crystal grains from the obtained SEM observation image, measuring their crystal grain size by the intercept method (k=1.78), and averaging the measured grain sizes. In the SEM observation image of the sintered body of this embodiment, the zirconia crystal grains can be distinguished from particles other than the zirconia crystal grains, such as particles of the Co-Fe solid solution, and pores, based on the difference in shading.

[0049] The sintered body of this embodiment is L * a * b * In the color system, lightness L * is 10 or less, and hue a * is between -2.00 and 2.00, and hue b * It is preferable that the color tone is greater than or equal to -2.00 and less than or equal to 5.00.

[0050] As a particularly preferred color tone of the sintered body of this embodiment, the following lightness L * , hue a * and b * Any combination of the above may be used.

[0051] Lightness L * : 0 or more and 9.0 or less, preferably 0 or more and 5.5 or less, More preferably, it is equal to or greater than 0 and less than 3.0. hue a* : -3.00 or more and 2.00 or less, Preferably -0.50 or more and 0.50 or less hue b * : -2.00 or more and 4.00 or less, Preferably, it is between -1.00 and 1.00. L * a * b * The color tone of the color system is obtained by measuring a sintered body with a surface roughness (Ra) of 0.02 nm or less using a method based on JIS Z 8722. The color tone can be evaluated as a color tone closer to that seen by the naked eye by determining it using the SCE method, which removes specular reflected light and measures diffuse reflected light.

[0052] The sintered body of this embodiment preferably has a biaxial bending strength (hereinafter also simply referred to as "biaxial bending strength") of 1400 MPa or more, more preferably 1700 MPa or more, measured in accordance with ISO / DIS 6872 and with a sample thickness of 1 mm. From the viewpoint of processability, the biaxial bending strength is preferably 3000 MPa or less, more preferably 2500 MPa or less.

[0053] The sintered body of this embodiment is a sintered body that has a color tone that is visually recognized as a colorless black, and can be used for various components such as luxurious jewelry and decorative components, for example, watch components and exterior components of portable electronic devices.

[0054] Next, a method for producing the sintered body of this embodiment will be described.

[0055] The method for producing a sintered body of this embodiment includes a sintering step of sintering a molded body containing a cobalt compound and an iron compound, the balance being zirconia, and the total content of cobalt converted as CoO and iron converted as Fe2O3 is more than 0.1 wt% and less than 3.0 wt%, in a reducing atmosphere. This makes it possible to produce a sintered body exhibiting a jet black color.

[0056] In the sintering step, a sintered body is obtained by sintering a molded body that contains a cobalt compound and an iron compound, with the remainder being zirconia, and in which the total of the content of cobalt converted into CoO and the content of iron converted into Fe2O3 is more than 0.1 wt% and less than 3.0 wt%.

[0057] The molded body to be subjected to the sintering step contains a cobalt compound and an iron compound, with the remainder being zirconia. The molded body preferably does not contain impurities other than unavoidable impurities. The molded body preferably does not contain zinc or chromium (i.e., the zinc content and chromium content are each 0% by weight, and each is preferably less than 0.1% by weight).

[0058] The cobalt compound is a compound containing cobalt (Co), and examples of the cobalt compound include at least one selected from the group consisting of tricobalt tetroxide (Co3O4), cobalt (III) oxide (Co2O3), cobalt (II) oxide (CoO), cobalt oxyhydroxide (CoOOH), cobalt hydroxide (Co(OH)2), cobalt nitrate (Co(NO3)2), cobalt chloride (CoCl2) and cobalt sulfate (CoSO4), and at least one selected from the group consisting of Co3O4, Co2O3, CoO and CoOOH is preferred.

[0059] The iron compound is a compound containing iron (Fe), and examples thereof include at least one selected from the group consisting of iron oxide (III, II) (Fe3O4), iron oxide (III) (Fe2O3), iron oxide (II) (FeO), iron oxyhydroxide (FeOOH), iron hydroxide (FeOH), iron nitrate (Fe(NO3)2), iron chloride (FeCl) and iron sulfate (FeSO4), and is preferably at least one selected from the group consisting of Fe3O4, Fe2O3, FeO and FeOOH.

[0060] The molded body may contain an aluminum compound. The aluminum compound is a compound containing aluminum (Al), and is, for example, alumina (Al2O3), aluminum hydroxide (Al(OH)3), aluminum chloride (AlCl3), aluminum isopropoxide (CH 21At least one selected from the group consisting of aluminum nitrate (Al(NO3)3), and aluminum oxide (Al(NO3)3) can be exemplified, and at least one of alumina and aluminum hydroxide is preferable.

[0061] The cobalt compound, iron compound and aluminum compound may be a composite oxide containing two or more selected from the group consisting of cobalt, iron and aluminum. The composite oxide may be one or more selected from the group consisting of CoFe2O4 (cobalt ferrite), CoAl2O4 (cobalt aluminate), FeAl2O4 and FeAlO3, with CoAl2O4 being preferred.

[0062] Zirconia (ZrO2) may be zirconia containing at least one selected from the group consisting of yttria, calcia, magnesia, vanadia, and titania, and is preferably yttria-containing zirconia, more preferably yttria-containing zirconia having an yttria content of 2 mol% or more and 4 mol% or less, and even more preferably yttria-containing zirconia having an yttria content of 2.5 mol% or more and 2.5 mol% or less.

[0063] The molded body may contain a compound containing a solid solution component or a precursor thereof (hereinafter, also referred to as a "solid solution component source"). Examples of such a compound include at least one selected from the group consisting of yttrium compounds, calcium compounds, magnesium compounds, vanadium compounds, and titanium compounds, and the compound is preferably at least one of an yttrium compound and a titanium compound, and more preferably a titanium compound.

[0064] The yttrium compound may be at least one selected from the group consisting of yttrium, yttrium chloride, and yttrium hydroxide, and is preferably at least one of yttrium or yttrium chloride. The calcium compound may be at least one selected from the group consisting of calcia, calcium chloride, and calcium hydroxide, and is preferably at least one of calcia or calcium chloride. The magnesium compound may be at least one selected from the group consisting of magnesia, magnesium chloride, and magnesium hydroxide, and is preferably at least one of magnesia or magnesium chloride. The vanadium compound may be at least one selected from the group consisting of vanadia, vanadium chloride, and vanadium hydroxide, and is preferably at least one of vanadia or vanadium chloride. The titanium compound may be at least one selected from the group consisting of titania, titanium chloride, titanium hydroxide, and titanium tetraisopropoxide, and is preferably at least one of titania or titanium hydroxide.

[0065] The compact has a total of the content of cobalt converted into CoO (cobalt content) and the content of iron converted into Fe2O3 (iron content) in the compact that is more than 0.1 wt% and less than 3.0 wt%, preferably more than 0.1 wt% and not more than 2.5 wt%, more preferably 0.12 wt% or more and 2.5 wt% or less, and particularly preferably 0.2 wt% or more and 1.5 wt% or less.

[0066] The ratio of the cobalt compound to the iron compound is arbitrary, but it is preferable that the weight ratio of the cobalt and iron in the compact, calculated as CoO and Fe2O3, CoO / (CoO+Fe2O3), is 0.10 or more and 0.99 or less, preferably 0.10 or more and 0.50 or less.

[0067] When the molded body contains an aluminum compound, the content of aluminum in the molded body calculated as Al2O3 is preferably 0.1 wt% or more and 3.0 wt% or less, more preferably 0.1 wt% or more and 2.5 wt% or less, more preferably 0.2 wt% or more and 2.5 wt% or less, even more preferably 0.1 wt% or more and 2.0 wt% or less, even more preferably 0.2 wt% or more and 2.0 wt% or less, even more preferably 0.1 wt% or more and 1.0 wt% or less, and particularly preferably 0.2 wt% or more and 1.0 wt% or less.

[0068] The content of the solute component source can be, for example, 2.0 mol% or more and 10.0 mol% or less. The content of the solute component source is the ratio (mol%) of each solute component source converted into oxide to the total of zirconia and each solute component source converted into oxide, and is a value calculated from [each solute component source (mol)] / [each solute component source (mol)+ZrO2(mol)]×100. For example, when the molded body contains an yttrium compound and a titanium compound, the content (mol%) of the yttrium compound is a value calculated from [Y2O3(mol)] / [Y2O3(mol)+ZrO2(mol)]×100, and the content (mol%) of the titanium compound is a value calculated from [TiO2(mol)] / [TiO2(mol)+ZrO2(mol)]×100.

[0069] For example, preferred contents of the sources of the solid solution components include at least any of the following.

[0070] Yttria content: 2.0 mol% or more and 4.0 mol% or less, preferably 2.5 mol% or more and 3.5 mol% or less Titania content: 1.0 mol% or more and 6.0 mol% or less, preferably 1.5 mol% or more and 4.8 mol% or less On the other hand, it is preferable that the molded body does not contain erbia (Er2O3) or ceria (CeO2) or at least one of their precursors, and the content of these is preferably below the detection limit (0 mol%), and taking into account measurement errors, etc., each of them can be less than 1 mol%.

[0071] The molded product may be one obtained by any method, and is preferably a molded product obtained by, for example, a process of mixing raw material compounds and molding the mixture.

[0072] The mixing may be any mixing method as long as the raw material compounds are homogenized. A preferred mixing method is wet mixing of the raw material compounds. A specific wet mixing method is mixing by at least one selected from the group consisting of a ball mill, a bead mill, and a stirring mill. Mixing by at least one of a ball mill and a bead mill is preferred, and mixing by a ball mill using zirconia balls with a diameter of 1.0 mm to 10.0 mm as a grinding medium is more preferred. In this embodiment, it is preferred to grind the raw material compounds when wet mixing the powders.

[0073] Any molding method can be applied as long as it is a method that can obtain a molded body of the desired shape. The molding method can be at least one selected from the group consisting of uniaxial pressing, cold isostatic pressing, slip casting, and injection molding. A preferred molding method is at least one of uniaxial pressing and cold isostatic pressing, and a molding method in which uniaxial pressing is followed by cold isostatic pressing is more preferred. An example of the conditions for uniaxial pressing is 20 MPa or more and 70 MPa or less, and an example of the conditions for cold isostatic pressing is 150 MPa or more and 250 MPa or less.

[0074] The shape of the molded body may be any shape depending on the purpose, and examples thereof include at least one shape selected from the group consisting of disk, columnar, cubic, rectangular, polyhedral, approximately polyhedral, plate, spherical, and approximately spherical.

[0075] In the sintering step, the compact is sintered in a reducing atmosphere to obtain a sintered body, which contains a solid solution of cobalt and iron.

[0076] In the sintering step, the compact is sintered in a reducing atmosphere. By sintering in a reducing atmosphere, both the formation of a solid solution and the precipitation of cobalt and iron proceed. If sintering is performed only in an oxidizing atmosphere, the color tone of the sintered body may differ or become uneven, and the sintered body of this embodiment may not be obtained stably.

[0077] In this embodiment, the reducing atmosphere may be an atmosphere using at least one of a reducing gas and a reducing heating element. The reducing gas may be a gas containing at least one of hydrogen and carbon monoxide. The reducing heating element may be a carbon heating element.

[0078] Preferred reducing atmospheres in this embodiment include those using a reducing heating element in an inert gas, and further include those using a carbon heating element in an argon or nitrogen atmosphere.

[0079] In the sintering step, the sintering method is arbitrary, and it is preferably either normal pressure sintering or pressure sintering, and more preferably pressure sintering. Heat sintering is preferably a hot press method or a hot isostatic press (hereinafter also referred to as "HIP") treatment, and more preferably HIP treatment. In this embodiment, normal pressure sintering is a method of sintering by simply heating the molded body without applying an external force during sintering, and pressure sintering is a method of sintering by applying an external force to the molded body during sintering and heating it.

[0080] The sintering temperature in the sintering step is 1300°C or higher and 1700°C or lower, preferably 1300°C or higher and 1675°C or lower, and more preferably 1450°C or higher and 1675°C or lower.

[0081] As preferred sintering conditions, the following conditions can be exemplified.

[0082] Sintering method: HIP processing Sintering atmosphere: at least one of argon and nitrogen, preferably argon Sintering temperature: 1300℃ to 1675℃ Preferably, 1450°C or higher and 1675°C or lower Sintering time: 0.5 to 5 hours Sintering pressure: 50MPa to 200MPa Preferably, 100 MPa or more and 175 MPa or less Heating element: Carbon heater The manufacturing method of this embodiment may include a pre-sintering step of sintering the compact in a non-reducing atmosphere to obtain a pre-sintered body, prior to the sintering step.

[0083] The sintering atmosphere in the pre-sintering step may be a non-reducing atmosphere, and may be either an oxidizing atmosphere or an inert atmosphere, and is preferably an oxidizing atmosphere, or more preferably an air atmosphere.

[0084] As long as sintering proceeds, any pre-sintering method may be used, but the pre-sintering method is preferably atmospheric sintering, and more preferably atmospheric sintering in an air atmosphere.

[0085] The pre-sintering conditions are exemplified as follows.

[0086] Pre-sintering method: Pressureless sintering Pre-sintering atmosphere: Air Pre-sintering temperature: 1300℃ to 1500℃ Preferably, the temperature is 1300°C or higher and 1450°C or lower. More preferably, 1300°C or higher and 1400°C or lower Pre-sintering time: 30 minutes to 5 hours When the manufacturing method of this embodiment includes a pre-sintering step, the pre-sintered body may be subjected to the sintering step instead of the compact.

[0087] The manufacturing method of this embodiment may include a heat treatment step of heat treating the sintered body at 650° C. or higher and 1100° C. or lower in an oxidizing atmosphere.

[0088] Any heat treatment method may be used as long as the heat treatment is performed in an oxidizing atmosphere. For simplicity, the heat treatment is preferably a method of simply heating the sintered body without applying an external force during the heat treatment (hereinafter also referred to as "normal pressure firing"). Normal pressure firing in an air atmosphere is more preferable.

[0089] The heat treatment temperature is preferably 650° C. or higher and 1100° C. or lower, and more preferably 700° C. or higher and 950° C. or lower. When zirconia contains two or more solid solution components, particularly when zirconia is zirconia containing yttria and titania, the heat treatment temperature is preferably 700° C. or higher and 950° C. or lower.

[0090] The heat treatment time may be from 1 hour to 48 hours at the above heat treatment temperature.

[0091] Particularly preferred conditions for the heat treatment step include the following.

[0092] Heat treatment method: Normal pressure firing Heat treatment atmosphere: Air Heat treatment temperature: 700℃ to 1050℃ Preferably, 800°C or higher and 950°C or lower Heat treatment time: 1 hour to 10 hours EXAMPLES

[0093] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.

[0094] The method for measuring the characteristics of the sintered body and powder of this embodiment will be described below.

[0095] (Actual density) The density of the sintered samples was measured by the Archimedes method. As a pretreatment, the sintered samples were boiled to remove any remaining bubbles on the surface of the sintered samples.

[0096] (Crystalline phase and monoclinic ratio) The XRD pattern of the surface of the sintered body sample was measured using a powder X-ray analyzer (device name: RINT Ultima III, manufactured by Rigaku Corporation) under the following measurement conditions.

[0097] Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Step width: 0.02° Scan speed: 5° / min Measurement range: 2θ=20° to 80° The crystal phase was determined from the obtained XRD pattern, and the monoclinic ratio of zirconia was measured by the following formula.

[0098] Monoclinic ratio (%) = [I m (111)+I m (11-1)] × 100 / [I m (111)+I m (11-1)+I t (111)+I c (111)] In the above formula, I m (111) is the surface intensity of the (111) plane of monoclinic zirconia, I m (11-1) is the surface intensity of the (11-1) plane of monoclinic zirconia, I t (111) is the surface intensity of the (111) plane of tetragonal zirconia, and I c (111) is the area intensity of the (111) plane of cubic zirconia.

[0099] (Color and reflectance) The color tone of the sintered body samples was measured according to the method of JIS Z 8722. A general color difference meter (device name: Spectrophotometer SD 3000, manufactured by Nippon Denshoku Industries Co., Ltd.) was used for the measurement. The measurement conditions were as follows, and the color tone and reflectance were obtained by the SCE method, which removes specular reflected light and measures diffuse reflected light.

[0100] Light source: D65 light source Viewing angle: 10° The sintered samples used were disk-shaped sintered bodies with a surface roughness of Ra = 0.02 μm or less, a thickness of 1 mm, and a diameter of 16 mm.

[0101] (Biaxial bending strength) The biaxial bending strength of the sintered samples was measured using a method based on ISO / DIS6872. A disk-shaped sintered sample with a diameter of 16 mm and a thickness of 1 mm was used for the measurement. The measurement was performed three times for the sintered samples prepared under the same conditions, and the average value was used as the biaxial bending strength.

[0102] (Average grain size) The average crystal grain size of the zirconia crystal grains in the sintered samples was measured by the intercept method.

[0103] As a pretreatment, the sintered samples were mirror-polished to a surface roughness Ra of 0.02 μm or less, and then thermally etched. Using a SEM, the surface of the sintered samples was observed at a magnification of 15,000 times to obtain an SEM observation diagram. From the obtained SEM observation diagram, 200 or more zirconia crystal grains (250 ± 50 grains) were randomly extracted, and their crystal grain sizes were measured by the intercept method (k = 1.78), and the average was taken as the average crystal grain size of the zirconia crystal grains.

[0104] (EPMA measurement and Co distribution measurement, etc.) Using an EPMA device (device name: EPMA1610, manufactured by Shimadzu Corporation), observation of the backscattered electron image and element mapping were performed under the following conditions.

[0105] Measurement method: wavelength dispersion type Accelerating voltage: 15kV Irradiation current: 300nA Analysis area: 51.2μm×51.2μm Number of fields of view: 3 Using the analysis software attached to the EPMA1610 (product name: EPMA system Ver.2.14, manufactured by Shimadzu Corporation), the obtained element mapping was binarized, and the number of areas where the intensity of the characteristic X-rays of cobalt or iron in the background was 1.5 times or more was counted. Here, for cobalt, the area where no particles were confirmed when the intensity of the mapping result was set to 120 counts was taken as the background, and binarization processing was performed with a threshold value of 1.5 times the average value. For iron, the area where no particles were confirmed when the intensity of the mapping result was set to 110 counts was taken as the background, and binarization processing was performed with a threshold value of 1.5 times the average value. The Co distribution, Fe distribution, most frequent Co distribution, and most frequent Fe distribution were obtained from the ratio of the number of each area to the number of areas measured.

[0106] The sintered body samples used were disk-shaped sintered bodies with a surface roughness of Ra = 0.02 μm or less, a thickness of 1 mm, and a diameter of 16 mm.

[0107] Example 1 Iron oxide powder, cobalt oxide powder, and 3 mol% yttria-containing zirconia powder were wet mixed with ethanol in a ball mill using zirconia balls to obtain a mixed powder containing 0.04 wt% iron oxide, 0.16 wt% cobalt oxide, and the remainder containing 3 mol% yttria-containing zirconia. The mixed powder was dried at 110°C in air and then sieved to obtain an agglomerated powder with an agglomerated particle size of 500 μm or less.

[0108] The agglomerated powder was uniaxially pressed using a die press at a pressure of 50 MPa, and then treated with a cold isostatic press at a pressure of 200 MPa to obtain a disk-shaped compact with a diameter of 20 mm and a thickness of 3 mm. The compact was sintered in air at 1350°C for 2 hours to obtain a primary sintered body. The density of the primary sintered body was 5.98 g / cm. 3 It was.

[0109] The primary sintered body was subjected to HIP treatment in an argon atmosphere at 1500°C, 150 MPa, and 1 hour to obtain a sintered body. The sintered body was then sintered in an air atmosphere at 900°C and normal pressure for 8 hours to obtain the sintered body of this example.

[0110] The results of elemental mapping of the sintered body of this example are shown in the table below.

[0111] [Table 1] The sintered body of this example is jet black, the Co distribution (5.5) is 0%, and no coarse particles were observed in the elemental mapping of cobalt. It can also be seen that the Fe distribution is smaller than the Co distribution.

[0112] The modal Co and Fe regions were 42.4% and 65.4%, respectively.

[0113] Example 2 The sintered body of this example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.40 wt% iron oxide and 0.10 wt% cobalt oxide, with the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 6.05 g / cm. 3 It was.

[0114] Example 3 The sintered body of this example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.25% by weight of iron oxide and 0.25% by weight of cobalt oxide, with the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 6.02 g / cm. 3 It was.

[0115] Figure 1 shows a backscattered electron image (Figure 1(a)), elemental mapping of iron (Figure 1(b)), and elemental mapping of cobalt (Figure 1(c)) of the sintered body of this example. It can be seen from Figure 1 that the sintered body of this example contains a Co-Fe solid solution, and that the Co-Fe solid solution is contained in the sintered body as particles of 0.1 to 3.5 μm.

[0116] Furthermore, elemental mapping of the zirconia crystal grains (the dotted circle in FIG. 1(a)) showed that the cobalt and iron contents of the zirconia crystal grains were below the measurement limit.

[0117] Example 4 The sintered body of this example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.10 wt% iron oxide and 0.40 wt% cobalt oxide, with the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 5.95 g / cm. 3 It was.

[0118] The results of elemental mapping of the sintered body of this example are shown in the table below.

[0119] [Table 2] The sintered body of this example is jet black in color, has a Co distribution (5.5) of 18.6%, and no coarse particles were observed in the elemental mapping of cobalt. It can also be seen that the Fe distribution is smaller than the Co distribution.

[0120] The modal Co and Fe regions were 38.4% and 59.9%, respectively.

[0121] Example 5 The sintered body of this example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.65 wt% iron oxide and 0.35 wt% cobalt oxide, with the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 5.96 g / cm. 3 It was.

[0122] Comparative Example 1 A sintered body of this comparative example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.02 wt% iron oxide and 0.08 wt% cobalt oxide, with the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 5.76 g / cm. 3 It was.

[0123] The results of elemental mapping of the sintered body of this comparative example are shown in the table below.

[0124] [Table 3] The sintered body of this comparative example had a Co distribution (5.5) of 0%, but did not contain iron, and no coarse particles were identified in the cobalt element mapping. However, it was light gray in color, not jet black.

[0125] Comparative Example 2 A sintered body of this comparative example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.50% by weight of cobalt oxide and the remainder being 3 mol% yttria-containing zirconia was used. The obtained sintered body had cracks.

[0126] Comparative Example 3 The sintered body of this comparative example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.50% by weight of iron oxide and the remainder being 3 mol% yttria-containing zirconia was used. The density of the primary sintered body was 6.02 g / cm 3 It was.

[0127] Comparative Example 4 A sintered body of this comparative example was obtained in the same manner as in Example 1, except that a mixed powder containing 1.95% by weight of iron oxide and 1.05% by weight of cobalt oxide, with the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 5.95 g / cm. 3 The obtained sintered body had cracks.

[0128] Element mapping was performed on the surface of the sintered body of this comparative example that did not contain defects such as cracks. The results are shown in the table below.

[0129] [Table 4] The sintered body of this comparative example had a Co distribution (5.5) of 35.3%, cobalt and iron contents of 3.0 mass% or more, and coarse particles were confirmed in the elemental mapping of cobalt. The sintered body had a non-uniform color tone with parts exhibiting dark gray and dark brown.

[0130] Comparative Example 5 A sintered body of this comparative example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.25% by weight of iron oxide and 0.25% by weight of cobalt oxide, with the remainder being 3 mol% yttria-containing zirconia, was used, and that the HIP treatment and the sintering after the HIP treatment were not performed. The density of the primary sintered body was 6.02 g / cm. 3 It was.

[0131] The evaluation results of Examples 1 to 5 and Comparative Examples 1 to 5 are shown in the table below.

[0132] [Table 5]

[0133] [Table 6] All of the sintered bodies of the examples were jet black in color and had a tetragonal main phase. In contrast, the sintered body containing 0.1% by weight of colorant (Comparative Example 1) and the sintered body not containing cobalt (Comparative Example 3) were dark gray and dark brown, respectively, and had a color tone that was not black.

[0134] Moreover, the sintered body that had not been sintered in a reducing atmosphere (Comparative Example 5) was light gray in color, and furthermore, the sintered body was dotted with spots and did not have a uniform color tone.

[0135] In both the sintered body containing no iron (Comparative Example 2) and the sintered body containing 3.0% by weight of colorant (Comparative Example 4), cracks occurred and a defect-free sintered body was not obtained.

[0136] Example 6 The sintered body of this example was obtained in the same manner as in Example 1, except that a mixed powder containing 0.10% by weight of iron oxide, 0.40% by weight of cobalt oxide, 0.25% by weight of alumina, and the remainder being 3 mol% yttria-containing zirconia, was used, using iron oxide powder, cobalt oxide powder, aluminum oxide (Al2O3) powder, and 3 mol% yttria-containing zirconia powder. The density of the primary sintered body was 6.04 g / cm3 It was.

[0137] Example 7 The sintered body of this example was obtained in the same manner as in Example 1, except that a mixed powder of iron oxide (Fe2O3) powder (purity 99% or more), cobalt aluminate (CoAl2O4) powder (purity 99% or more), and 3 mol% yttria-containing zirconia powder (purity 99.8% or more) was used so that the iron oxide was 0.10 wt%, the cobalt aluminate was 0.25 wt% (including 0.14 wt% Al2O3 and 0.11 wt% CoO), and the balance was 3 mol% yttria-containing zirconia. The density of the primary sintered body was 6.05 g / cm 3 It was.

[0138] Example 8 The sintered body of this example was obtained in the same manner as in Example 7, except that a mixed powder containing 0.10 wt% iron oxide, 0.50 wt% cobalt aluminate (including 0.28 wt% Al2O3 and 0.22 wt% CoO), and the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 6.05 g / cm 3 It was.

[0139] Example 9 The sintered body of this example was obtained in the same manner as in Example 7, except that a mixed powder containing 0.10 wt% iron oxide, 1.00 wt% cobalt aluminate (including 0.56 wt% Al2O3 and 0.44 wt% CoO), and the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 6.04 g / cm 3 It was.

[0140] Example 10 The sintered body of this example was obtained in the same manner as in Example 7, except that a mixed powder containing 0.10 wt% iron oxide, 2.00 wt% cobalt aluminate (including 1.12 wt% Al2O3 and 0.88 wt% CoO), and the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 6.01 g / cm 3 It was.

[0141] Example 11 The sintered body of this example was obtained in the same manner as in Example 7, except that a mixed powder containing 0.10 wt% iron oxide, 3.00 wt% cobalt aluminate (including 1.68 wt% Al2O3 and 1.32 wt% CoO), and the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 5.99 g / cm 3 It was.

[0142] The results of elemental mapping of the sintered body of this example are shown in the table below.

[0143] [Table 7] The sintered body of this example is jet black in color, has a Co distribution (5.5) of 23.7%, and no coarse particles were observed in the elemental mapping of cobalt. It can also be seen that the Fe distribution is smaller than the Co distribution.

[0144] Reference example 1 The sintered body of this example was obtained in the same manner as in Example 7, except that a mixed powder containing 0.10 wt% iron oxide, 5.00 wt% cobalt aluminate (including 2.8 wt% Al2O3 and 2.2 wt% CoO), and the remainder being 3 mol% yttria-containing zirconia, was used. The density of the primary sintered body was 5.86 g / cm 3 It was.

[0145] Example 6 11 and Reference Example 1 The physical properties of are shown in the table below.

[0146] [Table 8] Example 6 11 and Reference Example 1 The biaxial bending strength and color tone of are shown in the table below.

[0147] [Table 9] The sintered body (Example 3) containing 0.50% by weight of colorant and not containing alumina had a monoclinic ratio exceeding 1%, whereas the sintered body containing alumina had a monoclinic ratio of 0% even when the colorant content was 0.21% by weight or more and 2.22% by weight or less.

[0148] Furthermore, since all of the sintered bodies in the examples are jet black in color, it is clear that by setting the alumina content within this range (e.g., 0.2% by weight or more and 2.5% by weight or less), the formation of monoclinic zirconia crystals is suppressed without affecting the color tone of the sintered body.

[0149] Reference example 2 This was performed in the same manner as in Example 7, except that a mixed powder containing 0.10% by weight of iron oxide, 5.00% by weight of cobalt aluminate, and the balance being 3 mol% yttria-containing zirconia was used, and the HIP treatment temperature was 1650°C. reference The density of the primary sintered body was 5.84 g / cm 3 It was. reference The color of the sintered body in this example was jet black. The results are shown in the table below.

[0150] [Table 10] Reference example 3 This was carried out in the same manner as in Example 7, except that a mixed powder containing 0.10% by weight of iron oxide, 5.00% by weight of cobalt aluminate, and the balance being 3 mol% yttria-containing zirconia was used, and the temperature of the atmospheric sintering was set to 800°C. reference A sintered body of the example was obtained.

[0151] The density of the primary sintered body is 5.84g / cm 3 The sintered body of this example had a high density, high bending strength, and a jet black color.

[0152] Reference example 4 This was carried out in the same manner as in Example 7, except that a mixed powder containing 0.10% by weight of iron oxide, 5.00% by weight of cobalt aluminate, and the balance being 3 mol% yttria-containing zirconia was used, and the temperature of the atmospheric sintering was set to 1000°C. reference A sintered body of the example was obtained.

[0153] The density of the primary sintered body is 5.84g / cm 3 It was. reference The sintered body of the example had a high density, high bending strength, and a jet black color.

[0154] Reference example 3 and 4 The results are shown in the table below.

[0155] [Table 11] The sintered bodies obtained had a jet black color whether the temperature of the atmospheric firing was 800° C. or 1000° C. In addition, it can be seen that the color values ​​of the sintered bodies obtained by atmospheric firing at 800° C. were higher than those obtained by atmospheric firing at 1000° C.

[0156] Working Example 12 Iron oxide powder, cobalt oxide powder, titanium oxide powder, alumina powder, and 3 mol% yttria-containing zirconia powder were wet mixed with ethanol in a bead mill using zirconia beads to obtain a sintered body of this example in the same manner as in Example 1, except that a mixed powder containing 0.16 wt% iron oxide, 0.04 wt% cobalt oxide, 3.0 wt% titanium oxide (corresponding to a titania content of 4.69 mol%), 0.25 wt% aluminum oxide, and the remainder being 3 mol% yttria-containing zirconia was used. The density of the primary sintered body was 6.08 g / cm. 3 It was.

[0157] Working Example 13 The same as in the examples except that iron oxide powder, cobalt oxide powder, titanium oxide powder, alumina powder, and 3 mol% yttria-containing zirconia powder were wet-mixed with ethanol in a ball mill using zirconia balls. 12 The sintered body of this example was obtained in the same manner as in Example 1. The density of the primary sintered body was 5.94 g / cm 3 It was.

[0158] Working Example 12 and 13 The results of elemental mapping of the sintered body are shown in the table below.

[0159] [Table 12] Working Example 12 and 13 In each of the examples, the total of the iron content and the cobalt content is 0.2% by weight. Compared with these examples and Example 1, which has the same total of the iron content and the cobalt content, Examples 12 and 13 It can be seen that the values ​​of Co distribution and Fe distribution are small. 12 In the sintered body, the modal Co region and the modal Fe region were 87.0% and 74.4%, respectively, and it was observed that the Co-Fe solid solution confirmed by element mapping tends to become finer as the zirconia contains yttria and titania.

[0160] Working Example 14 Iron oxide powder, cobalt oxide powder, titanium oxide powder, alumina powder, and 3 mol% yttria-containing zirconia powder were wet mixed with ethanol in a ball mill using zirconia balls to obtain a sintered body of this example in the same manner as in Example 1, except that a mixed powder containing 0.4 wt% iron oxide, 0.1 wt% cobalt oxide, 1.0 wt% titanium oxide (corresponding to a titania content of 1.59 mol%), 0.25 wt% aluminum oxide, and the remainder being 3 mol% yttria-containing zirconia was used. The density of the primary sintered body was 6.02 g / cm. 3 It was.

[0161] Working Example 15 The sintered body of this example was obtained in the same manner as in Example 14, except that a mixed powder containing 0.4 wt% iron oxide, 0.1 wt% cobalt oxide, 2.0 wt% titanium oxide (corresponding to a titania content of 3.15 mol%), 0.25 wt% aluminum oxide, and the remainder being 3 mol% yttria-containing zirconia was used. The density of the primary sintered body was 6.00 g / cm. 3 It was.

[0162] Working Example 16 The examples are the same as those in the examples except that a mixed powder containing 0.4% by weight of iron oxide, 0.1% by weight of cobalt oxide, 3.0% by weight of titanium oxide (corresponding to 4.70 mol% titania content), 0.25% by weight of aluminum oxide, and the balance being 3 mol% yttria-containing zirconia was used. 14 The density of the primary sintered body was 5.96 g / cm 3 It was.

[0163] Working Example 17 The examples are the same as those in the examples except that a mixed powder containing 0.24% by weight of iron oxide, 0.06% by weight of cobalt oxide, 3.0% by weight of titanium oxide (corresponding to 4.69 mol% titania content), 0.25% by weight of aluminum oxide, and the balance being 3 mol% yttria-containing zirconia was used. 14 The sintered body of this example was obtained in the same manner as in Example 1. The density of the primary sintered body was 6.00 g / cm 3 It was.

[0164] Working Example 18 The examples are the same as those in the examples except that a mixed powder containing 0.4% by weight of iron oxide, 0.1% by weight of cobalt oxide, 1.0% by weight of titanium oxide (corresponding to 1.58 mol% titania content), and the remainder being 3 mol% yttria-containing zirconia was used. 14 The density of the primary sintered body was 6.06 g / cm 3 It was.

[0165] Working Example 19 The examples are the same as those in the examples except that a mixed powder containing 0.4% by weight of iron oxide, 0.1% by weight of cobalt oxide, 2.0% by weight of titanium oxide (corresponding to 3.14 mol% titania content), and the remainder being 3 mol% yttria-containing zirconia was used. 14 The density of the primary sintered body was 6.02 g / cm 3 It was.

[0166] Working Example 20 The examples are the same as those in the examples except that a mixed powder containing 0.4% by weight of iron oxide, 0.1% by weight of cobalt oxide, 3.0% by weight of titanium oxide (corresponding to a titania content of 4.69 mol%), and the remainder being 3 mol% yttria-containing zirconia was used. 14 The sintered body of this example was obtained in the same manner as in Example 1. The density of the primary sintered body was 5.99 g / cm 3 It was.

[0167] Working Example 14 ~ 20 The results of elemental mapping of the sintered body are shown in the table below.

[0168] [Table 13] Comparative Example 6 The examples are the same as those in the examples except that a mixed powder containing 0.08% by weight of iron oxide, 0.02% by weight of cobalt oxide, 3.0% by weight of titanium oxide (corresponding to 4.68 mol% titania content), 0.25% by weight of aluminum oxide, and the balance being 3 mol% yttria-containing zirconia was used. 14 The sintered body of this comparative example was obtained in the same manner as in Example 1. The density of the primary sintered body was 6.01 g / cm 3 It was.

[0169] The results of elemental mapping of the sintered body of this comparative example are shown in the table below.

[0170] [Table 14] The sintered body of this comparative example had a Co distribution (5.5) of 0%, but the total content of cobalt and iron was 0.1% by weight or less, and no coarse particles were observed in the elemental mapping of cobalt. However, the color was light gray, not jet black.

[0171] Working Example 12 ~ 20 The physical properties of Comparative Example 1 and Comparative Example 6 are shown in the table below.

[0172] [Table 15] Working Example 12 ~ 20 The biaxial bending strength and color tone of Comparative Example 1 and Comparative Example 6 are shown in the table below.

[0173] [Table 16] The sintered bodies of all the Examples were jet black in color, whereas the sintered body of Comparative Example 6, which contained 0.10% by weight of the coloring agent, was gray in color. * is greater than 9 and hue b * was over 5.

[0174] FIG. 3 shows an example. 13 4 shows elemental mapping of titanium and yttrium of the sintered body of

[0175] As shown in Fig. 3, titanium and yttrium show similar distributions and are both detected from the same particles. This shows that titania and yttria are dissolved in zirconia, and the zirconia is zirconia containing titania and yttria.

[0176] Comparative Example 7 The examples are the same as those in the examples except that a mixed powder containing 1.2% by weight of iron oxide, 0.3% by weight of cobalt oxide, 3.0% by weight of titanium oxide (corresponding to 4.68 mol% titania content), 0.25% by weight of aluminum oxide, and the balance being 3 mol% yttria-containing zirconia was used. 14The sintered body of this comparative example was obtained in the same manner as in Example 1. The density of the primary sintered body was 5.97 g / cm 3 The obtained sintered body had cracks.

[0177] The results of elemental mapping of the sintered body of this comparative example are shown in the table below.

[0178] [Table 17] The sintered body of this comparative example had a cobalt and iron content of less than 3.0% by weight, but the Co distribution (5.5) was 29.0%, and coarse particles were confirmed in the elemental mapping of cobalt. The sintered body had a non-uniform color tone, with parts showing dark gray and dark brown.

Claims

1. The composition contains a cobalt compound and an iron compound, with the balance being zirconia, and the content of cobalt calculated as CoO and the content of iron calculated as Fe 2 O 3 The present invention relates to a method for producing a sintered body, the method comprising: a pre-sintering step of sintering a compact in an air atmosphere at 1300° C. to 1500° C. under atmospheric pressure to obtain a pre-sintered body, the pre-sintered body being obtained by pressure-sintering the pre-sintered body in a reducing atmosphere at a sintering temperature of 1300° C. to 1675° C. and a sintering pressure of 50 MPa to 200 MPa. The present invention relates to a sintered body, the method comprising: 2 O 3 The total content of 5.5 μm or less calculated as 5.5 μm or less in element mapping by an electron beam microanalyzer is more than 0.1% by weight and 1.42% by weight or less. 2 A method for producing a sintered body, characterized in that the proportion of cobalt regions exceeding 25% is 0.05 or less.

2. 2. The method according to claim 1, wherein the reducing atmosphere is an atmosphere using at least one of a reducing gas and a reducing heating element.

3. The method according to claim 1 or 2, further comprising a heat treatment step of heat treating the sintered body at 650° C. or higher and 1100° C. or lower in an oxidizing atmosphere.

Citation Information

Patent Citations

  • Production of article based on black zirconia and ornament based on black zirconia produced especially thereby

    JP1995291630A

  • Black zirconia sintered compact, raw material powder for the same, and method of manufacturing them

    JP2006342036A

  • Powder for black zirconia sintered compact, sintered compact thereof and coloring agent

    JP2007308338A

  • Blue zirconia sintered body

    JP2016216289A

  • Black zirconia sintered body and use therefor

    JP2017077976A